Nilai-Nilai Filsafat Pendidikan Islam sebagai Landasan Pembinaan Moral Peserta Didik di Era Media Sosial - Ceshelya Astra; Aniska Septi Sabena; Fakhruddin Fakhruddin; Amrullah Amrullah (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2026)
Abstract: The increasing crisis of digital ethics in the social media era prompted this study to examine the values of Islamic educational philosophy as a basis for developing students' morals. The focus of the problem lies in moral disorientation characterized by cyberbullying, weak communication ethics, and the suboptimal internalization of religious values in students' digital activities. This study used a qualitative approach with a Narrative Literature Review design. Data sources were obtained through documentation studies including national and international journal articles, academic books, and previous research from the past five years. Data analysis was conducted using the Miles & Huberman interactive model, which includes data reduction, data presentation, and narrative conclusion drawing. The results of the study reveal five main themes: moral disorientation due to social media, the value of monotheism as spiritual control, the actualization of morals and etiquette in digital communication, the role model of educators as moral models, and the integration of Islamic digital literacy in education. These findings confirm that the values of Islamic educational philosophy, particularly the thoughts of Al-Ghazali, have strong relevance in shaping students' character in the digital space. The values of monotheism, morality, and etiquette serve as effective moral control mechanisms in suppressing negative behavior on social media. In conclusion, Islamic educational philosophy is not only normative but also applicable in addressing moral challenges in the digital era. This research contributes theoretically to the development of contemporary Islamic educational studies and provides practical implications for educators, parents, and policymakers in integrating Islamic values-based digital literacy. Further research is needed to explore students' empirical experiences in internalizing these values.Keywords: Islamic educational philosophy, student morality, social media, Al-Ghazali, Islamic digital literacy. Abstrak: Fenomena meningkatnya krisis etika digital di era media sosial mendorong kajian ini untuk menelaah nilai-nilai filsafat pendidikan Islam sebagai dasar pembinaan moral peserta didik. Fokus permasalahan terletak pada disorientasi moral yang ditandai dengan cyberbullying, lemahnya etika komunikasi, serta belum optimalnya internalisasi nilai religius dalam aktivitas digital peserta didik. Penelitian ini menggunakan pendekatan kualitatif dengan desain Narrative Literature Review. Sumber data diperoleh melalui studi dokumentasi yang meliputi artikel jurnal nasional dan internasional, buku akademik, serta penelitian terdahulu dalam lima tahun terakhir. Analisis data dilakukan menggunakan model interaktif Miles & Huberman yang mencakup reduksi data, penyajian data, dan penarikan kesimpulan secara naratif. Hasil kajian menunjukkan lima tema utama, yaitu disorientasi moral akibat media sosial, nilai tauhid sebagai kontrol spiritual, aktualisasi akhlak dan adab dalam komunikasi digital, keteladanan pendidik sebagai model moral, serta integrasi literasi digital Islami dalam pendidikan. Temuan ini menegaskan bahwa nilai-nilai filsafat pendidikan Islam, khususnya pemikiran Al-Ghazali, memiliki relevansi kuat dalam pembentukan karakter peserta didik di ruang digital. Nilai tauhid, akhlak, dan adab berfungsi sebagai mekanisme kontrol moral yang efektif dalam menekan perilaku negatif di media sosial. Kesimpulannya, filsafat pendidikan Islam tidak hanya bersifat normatif, tetapi juga aplikatif dalam menjawab tantangan moral di era digital. Penelitian ini berkontribusi secara teoritis dalam pengembangan kajian pendidikan Islam kontemporer, serta secara praktis memberikan implikasi bagi pendidik, orang tua, dan pembuat kebijakan dalam integrasi literasi digital berbasis nilai Islam. Kajian lanjutan diperlukan untuk mengeksplorasi pengalaman empiris peserta didik dalam internalisasi nilai tersebut.Kata kunci: filsafat pendidikan Islam, moral peserta didik, media sosial, Al-Ghazali, literasi digital Islami.